The role of the national road network in supporting interprovincial accessibility in Kalimantan : ISBN 978-630-95313-0-8 - Adi, Ari Sasmoko (Technium Books, 2025)
The book: The role of the national road network in supporting interprovincial accessibility in Kalimantan is published in Technium Books.